2015
DOI: 10.4238/2015.december.1.15
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis to evaluate the effectiveness of real-time PCR for diagnosing novel coronavirus infections

Abstract: ABSTRACT. Novel coronavirus (nCoV) belongs to the Coronaviridae family, which includes the virus that causes SARS, or severe acute respiratory syndrome. However, infection source, transmission route, and host of nCoV have not yet been thoroughly characterized. In some cases, nCoV presented a limited person-to-person transmission. Therefore, early diagnosis of nCoV may be of importance for reducing the spread of disease in public. Methods for nCoV diagnosis involve smear dyeing inspection, culture identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 24 publications
1
41
0
2
Order By: Relevance
“…Some scholars have found that RT‐PCR is effective for diagnosing novel coronavirus through meta‐analysis, is significantly better than smear‐dyeing inspection and culture identification, and it has become the gold standard for the diagnosis of coronavirus infections. However, there are inevitably many false positive and false negative results, which are often caused by sample contamination and damage to genetic material 18 . In 2003, some studies reported on the detection of virus particles in conjunctival secretions among SARS patients 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Some scholars have found that RT‐PCR is effective for diagnosing novel coronavirus through meta‐analysis, is significantly better than smear‐dyeing inspection and culture identification, and it has become the gold standard for the diagnosis of coronavirus infections. However, there are inevitably many false positive and false negative results, which are often caused by sample contamination and damage to genetic material 18 . In 2003, some studies reported on the detection of virus particles in conjunctival secretions among SARS patients 19 .…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of drawbacks to using cell culture compared to molecular methods, and many virology laboratories have opted to discontinue viral culture in the laboratory for these reasons. It is well established that cell culture has a lower sensitivity than molecular techniques (191,192), the turnaround time and hands-on time required to perform cell culture compared to molecular testing are increased, and the technical expertise for performing cell culture is often not available. Traditional tube cultures are slow and can take up to 10 days for detection of respiratory infections (36).…”
Section: Laboratory Detection Of Acute Respiratory Viruses the Role Omentioning
confidence: 99%
“…No additional SRs were identified on Google Scholar. Thus, 49 SRs 7‐55 were finally included in this study for methodological quality assessment. The flow diagram of the study selection process is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%